Developing Iraqi pre- service teachers' critical thinking skills and understanding of hamlet through reader response strategy - Abdulridha, Qayssar Abbas (2021)
Critical thinking is the ability to think correctly and systematically about what we believe and what we do. There is an emphasis on critical thinking in modern education around the world. Scholars worldwide have accepted that the primary objective of education is to help learners think more critically and accurately. Despite the importance of critical thinking, little effort has been made to develop critical thinking skills among Iraqi pre-service teachers. Therefore, this study investigates whether using a reader response strategy in teaching William Shakespeare's Hamlet can develop Iraqi pre-services teachers' critical thinking skills and enhance their understanding of the literary text. The study also attempts to investigate whether there is any significant correlation between the development of critical thinking and enhancement in understanding the literary text. Furthermore, it also investigates the types of literary responses produced by Iraqi pre-service teachers when they were taught Hamlet using the reader response strategy. The research was conducted at the Faculty of Education, Thiqar University in Iraq. The researcher used pre-post-tests one group quasi-experimental design. The findings of this study have revealed that the reader response strategy helps develop Iraqi pre-service teachers' critical thinking skills. There was a statistically significant increase at the p ≤ 0.05 level where the mean of pre-test total scores was 33.48 while the mean of post-test total scores was 45.90. Also, a reader response enhances their understanding of the literary text where mean of pre-test total scores was 27.69 while the mean of post-test total scores was 34.95. The findings also indicate a significant correlation between learner's development of critical thinking skills and enhancement of their understanding of the literary text (r = 0.40, p = 0.009). Reader response strategy also helps Iraqi pre-service teachers to produce numerous literary responses when learners were reading Hamlet. The outcomes of this study have various significant implications for EFL classrooms, particularly in Iraq. EFL literature teachers need to be trained on implementing the strategy of the reader response in EFL classrooms. Curriculum designers should guide teachers into utilizing reader response activities in the classroom. Moreover, the reader response strategy makes reading literature increasingly exciting and genuine for learners. Thus, it can be concluded that the reader response strategy is a positive and helpful method for developing of Iraqi pre-service teachers' critical thinking skills and enhancing their understanding of the literary text. Also, it fosters a meaning- seeking process during the reading of the literary text